Functionally graded dry adhesives based on f ilm-terminated silicone foam. (July 2017) - Liew, Kelvin; Shahsavan, Hamed; Zhao, Boxin
Abstract: A dry functionally graded adhesive (FGA) based on f ilm-terminated silicone foam was developed utilizing the foam's capacity of absorbing a large amount of energy to deliver high adhesion. The fabrication technique is based simply on sugar cube templating of common elastomers followed by film termination of the elastomer cubes using the same material. Dependences of the pull-off adhesive force and energy release rate on the preload and foam thickness were systematically investigated through a series of axisymmetric indentation/de-bonding tests. The contribution of the foam backing layer to the overall compliance and adhesion was analysed and discussed. The developed elastic f ilm-terminated structure has remarkable enhancement in pull-off force and work of adhesion, which can be employed in the transport of delicate objects as demonstrated in the pick and place of a silicon wafer. Furthermore, the proposed foam-based FGAs can be readily detached from the adherent surface by applying a slight shearing deformation. The research findings provide insights in understanding the role of mechanical graded properties in adhesion and can have technical implications in the development of a simple but effective dry adhesive material for mounting and transporting objects by automated robotic devices.